PUHSARANG CHURCH AS A RELIGIOUS TOURISM OBJECT IN KEDIRI DISTRICT 1999-2015 - Saputro, Moch Fajar Barep; Sugiyanto, Sugiyanto; Puji, Rully Putri Nirmala; Soepeno, Bambang; Triyanto, Jefri Rieski; Prasetyo, Guruh (JURNAL HISTORICA, 2022)
Puhsarang Church is a famous religious tourism object in Kediri District, located in Puhsarang Village 10 kilometers from the center of Kediri District. Having the unique architecture of buildings and religious facilities and the beauty of the natural panorama makes Puhsarang Church famous by tourists. The research objectives are: 1) knowing the background of the Puhsarang Church designated as a religious tourism object in 1999; 2) knowing the management of Puhsarang Church as a religious tourism object in 1995-2015. Research using historical methods include: Heuristics, Criticism, Interpretation, Historiography. The result of the research is that the construction of the Puhsarang Church was planned by Henricus Maclaine Pont and was built on the initiative of Pastor Wolters in 1936. Puhsarang Church underwent renovation in 1999, the expansion of the Puhsarang Church area and a new building was built. After being inaugurated the Puhsarang Church area was used as a religious tourism object. The management of the Puhsarang Church is under â€œYayasan Badan Pengelola Ziarah Gereja Puhsarangâ€. Suggestions for this research are: For other researchers, it can be used as a contribution of thoughts and references, for the government must participate in preserving historical heritage in their area.